MENUMBUHKAN SIKAP TOLERANSI KEHIDUPAN BERAGAMA MELALUI PENGAJARAN AGAMA KATOLIK STUDI KASUS PADA SMP RK DELI MURNI DISKI - Sinaga, Windy Vitaloca; Wilhelmus, Ola Rongan (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2022)
Cultivating tolerance in religious life can be taught through Catholic Religious Teaching in schools. One of the goals of teaching Catholicism in schools is to provide knowledge, to form an attitude of mutual acceptance, respect for differences in religion and other beliefs in society. The main problem in this study is the lack of tolerance in religious life in students at RK Deli Murni Diski Middle School. This can be seen from the reluctance of the students to congratulate other friends who are celebrating their religious holidays, and the lack of curiosity about the teachings of other religions and beliefs. The purpose of this study was to analyze the process of inculcating an attitude of religious tolerance in students through knowledge and appreciation of teaching Catholicism in schools. The research method used in this study is a mixed method consisting of quantitative and qualitative research methods. Methods of data analysis using descriptive statistics, correlation, and inductive analysis. The results of study showed that the majority or 86 (74.1%) respondents said that teaching Catholicism helps students respect and appreciate friends or teachers of other religions. The results of the correlation analysis between teaching Catholicism in schools and living harmony in the midst of religious differences also showed that there was a very significant correlation (.324**).